Prepatterning of differentiation-driven nuclear lamin A/C-associated chromatin domains by GlcNAcylated histone H2B - Rønningen, Torunn; Shah, Akshay; Oldenburg, Anja R.; Vekterud, Kristin; Delbarre, Erwan; Moskaug, Jan Øivind; Collas, Philippe (Genome Research, 2015)
Dynamic interactions of nuclear lamins with chromatin through lamin-associated domains (LADs) contribute to spatial arrangement of the genome. Here, we provide evidence for prepatterning of differentiation-driven formation of lamin A/C LADs by domains of histone H2B modified on serine 112 by the nutrient sensor O-linked N-acetylglucosamine (H2BS112GlcNAc), which we term GADs. We demonstrate a two-step process of lamin A/C LAD formation during in vitro adipogenesis, involving spreading of lamin A/C–chromatin interactions in the transition from progenitor cell proliferation to cell-cycle arrest, and genome-scale redistribution of these interactions through a process of LAD exchange within hours of adipogenic induction. Lamin A/C LADs are found both in active and repressive chromatin contexts that can be influenced by cell differentiation status. De novo formation of adipogenic lamin A/C LADs occurs nonrandomly on GADs, which consist of megabase-size intergenic and repressive chromatin domains. Accordingly, whereas predifferentiation lamin A/C LADs are gene-rich, post-differentiation LADs harbor repressive features reminiscent of lamin B1 LADs. Release of lamin A/C from genes directly involved in glycolysis concurs with their transcriptional up-regulation after adipogenic induction, and with downstream elevations in H2BS112GlcNAc levels and O-GlcNAc cycling. Our results unveil an epigenetic prepatterning of adipogenic LADs by GADs, suggesting a coupling of developmentally regulated lamin A/C-genome interactions to a metabolically sensitive chromatin modification.